The Use Of Flipped Classroom To Improve Grammatical Mastery Using Whastsapp Group Discussion - Achmad Fauzi Masyhadi; Yudhi Arifani; Candra Hadi Asmara (Universitas Muhammadiyah Gresik, 2022)
Flipped classroom is the replacement of direct instruction with video lessons and the encouragement of students to focus on important learning activities with their teachers inside the classroom. Although there is an information gap concerning the flipped classroom, it can be clarified as a personalised education where students take responsibility of their own learning. In addition, the flipped classroom allows the teacher to be a facilitator and also increases the interaction and personal contact time between teacher and student. The flipped classroom is also explained as the establishment of problem-based learning inside the class by replacing direct instruction with video lessons in order to provide instructional content that can be accessed by students whenever and wherever it is required This study was to investigate the significant effect the Use of Flipped Classroom to Improve Grammatical Mastery Using Whastsapp Group Discussion at Seventh Grade. The researcher chooses the students of sevent grade at MTs. Nurul Islam Gresik to conduct this study. The researcher used Non randomize sampling . This means that the selection of first graders of Islamic Junior High School Pongangan Gresik is to know the level and considering well. This technique is based on an explanation of the exam score by the teacher.,. The researcher decided to use 7B as the experimental group and 7C as the control group. Both of the class consisted of 32 students. So, the numbers of the participant of this study 64 students.